Depression and executive dysfunction contribute to a metamemory deficit among individuals with methamphetamine use disorders. (January 2015) - Casaletto, K.B.; Obermeit, L.; Morgan, E.E.; Weber, E.; Franklin, D.R.; Grant, I.; Woods, S.P.; ,
Abstract: Objective: Chronic methamphetamine (MA) use is associated with moderate deficits in learning and memory, but the extend to which MA users are aware of such memory deficits (i.e., metamemory) is not known.Methods: In the current study, 195 participants with lifetime MA use diagnoses (MA +) and 195 non-MA-using comparison subjects (MA -) underwent comprehensive neuropsychiatry research assessments, including performance-based and self-report measures of episodic memory.Results: MA use disorders, major depressive disorder (MDD), and their interaction were uniquely associated with metamemory functioning, such that MDD increased the likelihood of a metamemory deficit among MA + participants. Within the MA group, individuals who over-estimated their memory abilities demonstrated greater executive dysfunction and lower cognitive reserve.Conclusions: Chronic MA use is associated with reduced awareness of objective deficits in memory acquisition and recall, which is particularly exacerbated by the presence of major depression. Efforts to enhance metamemory accuracy and deployment of compensatory mnemonic strategies may benefit substance abuse treatment outcomes. Highlights: Compared awareness of memory deficits (metamemory) in methamphetamine (MA) users vs. non-users MA users were more impaired, but less aware of memory impairments than non-users MA and depression interacted such that MA users with depression had the most inaccurate metamemory Poor metamemory was associated with executive dysfunction and lower cognitive reserve in MA users